2008
DOI: 10.1016/j.bbabio.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of thermogenesis in flowering Araceae: The role of the alternative oxidase

Abstract: The inflorescences of several members of the Arum lily family warm up during flowering and are able to maintain their temperature at a constant level, relatively independent of the ambient temperature. The heat is generated via a mitochondrial respiratory pathway that is distinct from the cytochrome chain and involves a cyanide-resistant alternative oxidase (AOX). In this paper we have used flux control analysis to investigate the influence of temperature on the rate of respiration through both cytochrome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 50 publications
1
64
1
3
Order By: Relevance
“…The extent to which other organic acids, such as succinate, are able to stimulate AmAOX1e and SgAOX remains to be investigated. However, it would be tempting to speculate that homoeothermic plants such as skunk cabbage and sacred lotus utilize their metabolites for fine control of the AOX-mediated oxygen consumption and also that the metabolic pathways that regulate the mitochondrial pool of pyruvate or succinate may play an important role in thermoregulation in these plants, whereas in A. maculatum and S. guttatum, the expression levels of pyruvate-insensitive AOX protein per se regulate their thermogenic activities, as proposed previously (Wagner et al, 2008). Alternatively, because pyruvate has been shown recently to stabilize the active conformation of purified AOX, which supports an exclusive effect of pyruvate on the enzyme's apparent V max in the mitochondria of A. maculatum (CarrĂŠ et al, 2011), cellular metabolites including pyruvate may have a more general role to protect and/or stabilize the active conformation of AOX protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent to which other organic acids, such as succinate, are able to stimulate AmAOX1e and SgAOX remains to be investigated. However, it would be tempting to speculate that homoeothermic plants such as skunk cabbage and sacred lotus utilize their metabolites for fine control of the AOX-mediated oxygen consumption and also that the metabolic pathways that regulate the mitochondrial pool of pyruvate or succinate may play an important role in thermoregulation in these plants, whereas in A. maculatum and S. guttatum, the expression levels of pyruvate-insensitive AOX protein per se regulate their thermogenic activities, as proposed previously (Wagner et al, 2008). Alternatively, because pyruvate has been shown recently to stabilize the active conformation of purified AOX, which supports an exclusive effect of pyruvate on the enzyme's apparent V max in the mitochondria of A. maculatum (CarrĂŠ et al, 2011), cellular metabolites including pyruvate may have a more general role to protect and/or stabilize the active conformation of AOX protein.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the cytochrome c oxidase, AOX does not pump protons (Moore et al, 1978), and this allows the dramatic drop in free energy between ubiquinol and oxygen to be dissipated as heat (Vanlerberghe and McIntosh, 1997;Albury et al, 2009). Electron paramagnetic resonance studies have shown that the AOX active site comprises a binuclear iron center (Berthold et al, 2002;Moore et al, 2008), and persuasive Fourier transform infrared analysis has further indicated that the AOX belongs to the class of membrane-bound diiron carboxylate proteins (Berthold et al, 2002;Berthold and Stenmark, 2003;MarĂŠchal et al, 2009).…”
mentioning
confidence: 99%
“…As mentioned earlier, this protein, similar to the UCP, provides a means to relax the coupling between respiration and ATP production and it appears to be particularly important under stress (359). A small number of thermogenic plants use AOX in order to generate heat from respiration (228,370,377); however, given the limited range of plants possessing this capacity, the function of AOX should differ from this in most species. Specific AOX gene family members are strongly induced at the transcript and protein level by complex III or complex IV dysfunction (167,361), suggesting that AOX expression is highly responsive to insufficient cytochrome pathway capacity downstream of the ubiquinone pool.…”
Section: The Metcmentioning
confidence: 99%
“…Importantly, transcript abundance is not necessarily correlated with protein abundance or enzyme activity, and expression of AOX and pUCP in nonthermogenic and thermogenic tissues of P. bipinnatifidum has not been investigated. Coexpression of both pUCP and AOX proteins has been reported in thermogenic tissues of some other aroids, suggesting the possibility that both may play a role in thermogenesis (Onda et al, 2008;Wagner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Araceae; Lance, 1974). The Araceae contains more thermogenic species than any other family (Meeuse, 1975;Meeuse & Raskin, 1988;Gibernau et al, 2005), and has attracted much attention from researchers aiming to understand heating mechanisms (Wagner et al, 1998(Wagner et al, , 2008Ito et al, 2003a,b;Crichton et al, 2005;Ito & Seymour, 2005;Onda et al, 2008), or to characterize the ecological significance of thermogenesis in plant-pollinator interactions (Gottsberger, 1999;Gibernau & BarabĂŠ, 2002). Among thermogenic arums, the capacity for heat generation differs markedly, from approx.…”
Section: Introductionmentioning
confidence: 99%